Preparation method of magnesium alloy surface composite film

By pretreating and hydrothermal reaction on the magnesium alloy substrate, LDHs sheets containing zinc sites were formed and zinc oxide nanocolumns were grown, which solved the problem of low density of the existing composite film on the surface of magnesium alloy, and significantly improved the composite film. Corrosion resistance and corrosion resistance.

CN119465125APending Publication Date: 2025-02-18GUANGZHOU JIANCHI BIOTECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411477570.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing magnesium alloy surface composite film has low density, resulting in limited barrier effect on corrosive media and further improvement in corrosion resistance.

Method used

After pretreatment of the magnesium alloy substrate, it is impregnated in an alkaline solution, and then a first hydrothermal reaction is performed in a first hydrothermal growth solution containing zinc ions to form LDHs sheets containing zinc sites. Then a second hydrothermal reaction is carried out in a second hydrothermal growth solution containing zinc nitrate hexahydrate and polyethyleneimine to regulate the growth of the zinc oxide nanocolumns perpendicular to the LDHs sheets, thereby achieving the sealing of irregular micro-vacuums of LDHs.

Benefits of technology

The density of the composite film on the surface of the magnesium alloy is improved, the micro void size is significantly reduced, and the corrosion resistance and corrosion resistance of the composite film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005096518800000011
    Figure HDA0005096518800000011
  • Figure HDA0005096518800000012
    Figure HDA0005096518800000012
  • Figure HDA0005096518800000021
    Figure HDA0005096518800000021
Patent Text Reader

Abstract

The invention discloses a preparation method of a magnesium alloy surface composite film, and belongs to the technical field of magnesium alloy surface treatment. According to the preparation method, a pretreated magnesium alloy substrate is firstly soaked in an alkaline solution, then the magnesium alloy substrate is sequentially placed in a first hydrothermal growth solution and a second hydrothermal growth solution to be subjected to a hydrothermal reaction, and in the first hydrothermal reaction, a zinc site, namely a nucleation point for in-situ growth of a zinc oxide nanorod, can be formed while an LDHs sheet is formed; in the second hydrothermal reaction, a zinc site formed in the first hydrothermal reaction is used as a nucleation point for in-situ growth of the zinc oxide nanorod, so that the growth of the zinc oxide nanorod array perpendicular to the LDHs sheet can be effectively regulated and controlled, a better sealing effect on the LDHs irregular micro-gap is realized, the LDHs membrane gap is shrunk to several nanometers, and the LDHs membrane has good sealing performance. Furthermore, the difference between the gap sizes is reduced, and the corrosion resistance of the surface composite film is improved. In addition, the preparation method provided by the invention is simple to operate and beneficial to actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloy surface treatment, and in particular relates to a method for preparing a magnesium alloy surface composite film. Background Art

[0002] Due to the diversity of LDHs building blocks, the controllability of layered structures, the unique interlayer anion exchange and high biocompatibility, magnesium alloy-based LDHs membranes have rapidly developed into new functional membrane materials and are highly favored in basic research on corrosion protection and biomedical materials applications. However, the inherent oriented growth tendency of LDHs microchips perpendicular to the substrate leads to the interlacing of adjacent LDHs sheets to form abundant micro-voids, which greatly reduces the density of the LDHs membrane and usually shows high sensitivity to local corrosion (pitting and filamentary corrosion). Therefore, the service life of the functionalized membrane layer on the surface of magnesium alloys depends to a great extent on the barrier / protection effect of the LDHs membrane on the corrosive medium.

[0003] Generally, the anti-corrosion mechanism of corrosion protection film mainly relies on the physical barrier effect of the film layer, so its corrosion protection effect is mainly determined by the density, uniformity and thickness of the film. From the perspective of the physical barrier of corrosion protection, the common strategy is to construct a dense physical barrier film layer to prevent corrosive substances from penetrating downward to the metal surface. It is generally believed that the denser the film, that is, the smaller the density and size of the cracks or pores, the more uniform the film layer, and the better the corrosion resistance of the film layer; the thicker the film layer, the stronger the corrosion protection durability. For example, Wu et al. also deposited Al 2 O 3 Nanoparticles were filled into the gaps of MgAl-LDHs film, and Al 2 O 3 Nanoparticles show a synergistic effect on the wear resistance and corrosion resistance of LDHs film. 2 O 3 How nanoparticles improve the corrosion resistance of LDHs composite coatings remains unclear. In addition, Yan et al. studied the effect of two-dimensional graphene sheets on the corrosion resistance of LDHs / MoO 4 and reported the effectiveness of graphene on the corrosion resistance of LDHs, where graphene acts as part of an impermeable and inert layer against water molecules and aggressive Cl - Although a denser composite membrane structure is obtained by depositing an inorganic film layer or / and nanoparticles in the gaps of the LDHs membrane, there is still a random microporous structure (random growth of particles), and its corrosion resistance is not significantly improved. At the same time, the LDHs membrane is also sealed. However, when the gaps in the LDHs membrane are sealed, the disordered deposition of nanoparticles is still prone to microvoids. Relative to the corrosive medium, the microvoids are "macro transmission channels." Therefore, the barrier effect on the corrosive medium is still limited, and the corrosion resistance / corrosion inhibition performance needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a method for preparing a magnesium alloy surface composite film with high density, few micro-voids, and excellent and lasting corrosion resistance.

[0005] To achieve the above object, in a first aspect of the present invention, the present invention provides a method for preparing a composite film on the surface of a magnesium alloy, the preparation method comprising the following steps:

[0006] (1) Pretreating the magnesium alloy substrate;

[0007] (2) immersing the magnesium alloy substrate pretreated in step (1) in an alkaline solution, followed by pickling, water washing, and drying;

[0008] (3) placing the magnesium alloy dried in step (2) in a first hydrothermal growth solution to perform a first hydrothermal reaction, and washing and drying after the first hydrothermal reaction is completed;

[0009] (4) placing the magnesium alloy dried in step (3) in a second hydrothermal growth solution for a second hydrothermal reaction, and washing and drying after the second hydrothermal reaction is completed;

[0010] The solutes of the first hydrothermal growth solution include zinc salt, urea and sodium ethylenediaminetetraacetate, and the solvent is deionized water;

[0011] The solute of the second hydrothermal growth solution includes zinc nitrate hexahydrate and polyethyleneimine, and the solvent is deionized water.

[0012] The present invention can obtain a densified magnesium alloy surface composite film by immersing the pretreated magnesium alloy substrate in an alkaline solution first, and then placing it in a first hydrothermal growth liquid and a second hydrothermal growth liquid in sequence for hydrothermal reaction. The obtained composite film has excellent corrosion resistance.

[0013] Specifically, the present invention first immerses the substrate in an alkaline solution to roughen the surface of the magnesium alloy substrate. In the subsequent first hydrothermal reaction, the substrate is placed in a first hydrothermal growth solution containing zinc ions, urea and sodium ethylenediaminetetraacetate. While forming LDHs sheets, due to the addition of zinc ions, LDHs sheets containing "zinc sites" can be formed simultaneously. Then, a second hydrothermal reaction is carried out in a second growth solution containing zinc nitrate hexahydrate and polyethyleneimine. Since Zn is mainly doped in the LDHs layer in the form of Zn-O bonds (similar to the ZnO structure), active sites are provided for the growth of ZnO nanocolumns on the surface of the LDHs sheets, effectively regulating the growth of the zinc oxide nanocolumn array perpendicular to the LDHs sheets. Therefore, on the one hand, the density of the LDHs film is improved by growing zinc oxide in the micro-voids of the LDHs film; on the other hand, the zinc oxide nanocolumn array prepared by pre-inserting active sites on the surface of the LDHs sheet can achieve a better sealing effect on the irregular micro-voids of LDHs, which can reduce the voids in the LDHs film to a few nanometers, thereby reducing the differences in void sizes and improving the anti-corrosion performance of the surface composite film.

[0014] As a preferred embodiment of the preparation method of the present invention, the magnesium alloy includes any one of AZ31 and AZ91.

[0015] As a preferred embodiment of the preparation method of the present invention, in the step (1), the pretreatment includes mechanically polishing the magnesium alloy substrate using silicon carbide sandpaper, washing with acetone, ethanol and deionized water in sequence after polishing, and then drying.

[0016] Preferably, the mechanical polishing is performed using 600#, 1500# and 3000# silicon carbide sandpaper in sequence.

[0017] Preferably, the ethanol is an ethanol solution with a mass percentage of 95%.

[0018] As a preferred embodiment of the preparation method of the present invention, in the step (2), the solute of the alkaline solution includes potassium hydroxide and / or sodium hydroxide, and the molar concentration of the solute is 0.5-2 mol / L.

[0019] As a preferred embodiment of the preparation method of the present invention, in the step (2), the immersion temperature is 70-90° C., and the immersion time is 2-4 hours.

[0020] Exemplarily, the immersion temperature can be any point value or any range value between 70-90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C, etc.; the immersion time can be any point value or any range value between 2-4h, such as 2h, 2.5h, 3h, 3.5h, 4h, etc.

[0021] The present invention has found that when the solute of the alkaline solution is further selected to include potassium hydroxide and / or sodium hydroxide and the molar concentration of the solute is 0.5-2 mol / L, and when the temperature and time of immersion in the alkaline solution are further selected to be within the above range, the surface of the magnesium alloy can be better roughened, which can facilitate the subsequent hydrothermal reaction film formation, thereby obtaining a composite film with a high degree of densification, thereby improving the corrosion resistance of the composite film.

[0022] As a preferred embodiment of the preparation method of the present invention, the zinc salt includes at least one of zinc nitrate and zinc acetate.

[0023] As a preferred embodiment of the preparation method of the present invention, in the step (3), in the first hydrothermal growth solution, the molar concentration of zinc ions is 1-3 mmol / L, the molar concentration of urea is 30-50 mmol / L, and the molar concentration of sodium ethylenediaminetetraacetate is 10-50 mmol / L; the pH value of the first hydrothermal growth solution is 9.5-10.5.

[0024] Preferably, the pH value of the first hydrothermal growth liquid is adjusted by using an ammonia solution with a mass percentage of 1-5%.

[0025] Preferably, the first hydrothermal growth solution is prepared by dissolving zinc salt and urea in boiled and cooled deionized water, then adding sodium ethylenediaminetetraacetate, and then adjusting the pH value to 9.5-10.5 using an ammonia solution.

[0026] As a preferred embodiment of the preparation method of the present invention, in the step (3), the temperature of the first hydrothermal reaction is 90-110° C., and the time of the first hydrothermal reaction is 12-24 h.

[0027] Exemplarily, the temperature of the first hydrothermal reaction can be any point value or any two points in the range between 90-110°C, such as 90°C, 95°C, 100°C, 105°C, 110°C, etc.; the time of the hydrothermal reaction can be any point value or any two points in the range between 12-24h, such as 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.

[0028] The present invention has found that when the molar concentration of the solute in the first hydrothermal growth solution is further selected to be within the range given by the present invention, and the temperature and time of the first hydrothermal reaction are within the above range, LDHs sheets can be effectively generated, and zinc sites can be formed between the LDHs sheets, providing nucleation points for the subsequent in-situ growth of zinc oxide nanocolumns, thereby facilitating the effective regulation of the growth of the array of zinc oxide nanocolumns perpendicular to the LDHs sheets in the second hydrothermal reaction, thereby forming a good sealing effect on the surface of the magnesium alloy, and improving the corrosion resistance of the composite film.

[0029] Preferably, the first hydrothermal reaction is a sealed reaction in a stainless steel autoclave lined with polytetrafluoroethylene.

[0030] As a preferred embodiment of the preparation method of the present invention, in the step (3), the drying temperature is 55-65° C., and the drying time is 1.5-2.5 h.

[0031] As a preferred embodiment of the preparation method of the present invention, in the step (4), the molar concentration of zinc nitrate hexahydrate in the second hydrothermal growth solution is 10-30 mmol / L; and the pH value of the second hydrothermal growth solution is 8-9.

[0032] Preferably, the second hydrothermal growth solution is prepared by dissolving zinc nitrate hexahydrate in boiled and cooled deionized water, then mixing it with polyethyleneimine, and then adjusting the pH value to 8-9 using an ammonia solution.

[0033] Preferably, the molar ratio of zinc nitrate hexahydrate to polyethyleneimine is 1:1.

[0034] As a preferred embodiment of the preparation method of the present invention, in the step (4), the temperature of the second hydrothermal reaction is 85-95° C., and the time of the second hydrothermal reaction is 4-8 h.

[0035] Exemplarily, the temperature of the second hydrothermal reaction can be any point value or any two points in the range between 85-95°C, such as 85°C, 87°C, 89°C, 91°C, 93°C, 95°C, etc.; the time of the hydrothermal reaction can be any point value or any two points in the range between 4-8h, such as 4h, 5h, 6h, 7h, 8h, etc.

[0036] The present invention has found that when the molar concentration of the solute in the second hydrothermal growth solution is further selected to be within the range given by the present invention, and the temperature and time of the second hydrothermal reaction are within the above range, a dense zinc oxide nanocolumn array composite structure can be formed on the surface of LDHs containing Zn sites formed by the first hydrothermal reaction, and the formed zinc oxide nanocolumns are covalently bonded to the LDHs sheets, that is, there is a strong binding force between the two, and the zinc oxide nanocolumns are arranged more neatly, thereby achieving a better sealing effect on the irregular gaps of LDHs, thereby improving the corrosion resistance of the composite film.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The present invention immerses the pretreated magnesium alloy substrate in an alkaline solution first, and then sequentially places it in a first hydrothermal growth liquid and a second hydrothermal growth liquid for hydrothermal reaction, so that an LDHs sheet containing Zn sites can be formed in the first hydrothermal reaction; then in the second hydrothermal reaction, the Zn sites on the surface of the LDHs sheet provide nucleation points for the growth of zinc oxide nanocolumns on its surface, effectively regulating the array of zinc oxide nanocolumns to grow perpendicular to the LDHs sheet, achieving a better sealing effect on the irregular micro-voids of LDHs, reducing the voids of the LDHs film to a scale of several nanometers, thereby reducing the difference between the void sizes and improving the corrosion resistance of the surface composite film. In addition, the preparation method provided by the present invention is simple to operate and is conducive to actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the process for preparing the composite film on the surface of the magnesium alloy in Example 1;

[0040] Figure 2 This is a SEM image of the magnesium alloy surface after treatment in step (3) in Example 1;

[0041] Figure 3 This is the EDS spectrum of the magnesium alloy surface film after treatment in step (3) in Example 1;

[0042] Figure 4 The SEM image (500 nm) of the composite film on the surface of the magnesium alloy prepared after the treatment in step (4) in Example 1;

[0043] Figure 5 The SEM image (100 nm) of the composite film on the surface of the magnesium alloy prepared after the treatment in step (4) in Example 1;

[0044] Figure 6 The XRD pattern of the composite film on the surface of the magnesium alloy prepared after the treatment in step (4) in Example 1;

[0045] Figure 7 is a SEM image of the composite film on the surface of the magnesium alloy prepared in Comparative Example 1;

[0046] Figure 8 is a SEM image of the composite film on the surface of the magnesium alloy prepared in Comparative Example 2;

[0047] Fig. 9 is a SEM image of the composite film on the surface of the magnesium alloy prepared in Comparative Example 3;

[0048] Fig.10 Result diagram of the anodic polarization curve of the magnesium alloy surface composite film prepared in Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0049] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0050] Unless otherwise specified, the reagents, methods and equipment used in the present invention are all conventional reagents, methods and equipment in the art; and unless otherwise specified, the raw materials used in parallel experiments are from the same batch of raw materials.

[0051] Example 1

[0052] The present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The schematic flow chart of the preparation method is as follows: Figure 1 As shown, the following steps are included:

[0053] (1) A magnesium alloy (AZ31) was mechanically polished with 600#, 1500#, and 3000# silicon carbide sandpaper in sequence, and then ultrasonically cleaned in acetone, 95% ethanol solution, and deionized water in sequence. After cleaning, it was blown dry to obtain a pre-treated magnesium alloy substrate;

[0054] (2) placing the magnesium alloy substrate pretreated in step (1) in an alkaline solution (the alkaline solution is a 1 mol / L sodium hydroxide solution) and immersing it at 80° C. for 4 h; after immersion, taking it out and ultrasonically cleaning it with deionized water, and then drying it;

[0055] (3) The magnesium alloy dried in step (2) is vertically immersed in a first hydrothermal growth solution (in the first hydrothermal growth solution, zinc nitrate hexahydrate is 1 mmol / L, urea is 40 mmol / L, sodium ethylenediaminetetraacetate is 10 mmol / L, the solvent is deionized water, and the pH value of the first hydrothermal growth solution is adjusted to 10.5 with 1 wt% ammonia solution), and then the system is transferred to a stainless steel autoclave lined with tetrafluoroethylene, and then the autoclave is sealed and placed in an oven at 105° C. for 20 h to perform a first hydrothermal reaction; after the first hydrothermal reaction is completed, the magnesium alloy is taken out and washed with boiled and cooled deionized water, and finally dried in an oven at 60° C. for 2 h; the surface micromorphology of the dried magnesium alloy is observed, and its SEM image is as shown in Figure 2 As shown, from Figure 2 It can be seen that a typical cross-linked LDHs thin film with a size of about 0.5 to 1.5 μm grows vertically on the surface of the magnesium alloy. The LDHs sheet shows a good hexagonal sheet-like LDHs structure. The formed film is further analyzed by EDS, and the obtained EDS spectrum is shown in the figure below. Figure 3 As shown, from Figure 3 It can be seen that the film shows zinc components, which means that this step introduces zinc while forming the LDHs layer;

[0056] (4) The magnesium alloy dried in step (3) is vertically immersed in a second hydrothermal growth solution (the preparation method of the second hydrothermal growth solution is: mixing a 20 mmol / L hexahydrate zinc nitrate deionized water solution and polyethyleneimine, wherein the molar ratio of hexahydrate zinc nitrate to polyethyleneimine is 1:1, and then adjusting the pH value of the second hydrothermal growth solution to 8.5 with a 1 wt % ammonia solution), and then transferring the system to a stainless steel autoclave lined with tetrafluoroethylene, and then sealing the autoclave and placing it in an oven at 95° C. for 4 h to perform a second hydrothermal reaction; after the second hydrothermal reaction is completed, the magnesium alloy is cooled to room temperature, and the magnesium alloy is taken out and washed with deionized water that has been boiled and cooled, and finally dried naturally; the surface micromorphology of the magnesium alloy after drying is observed, and its SEM image is as shown in the figure Figure 4-5 As shown, from Figure 4-5 It can be seen that the nano-columnar material grows vertically to the LDHs surface in a closely arranged manner (array), and the nano-columns span the gaps between the LDHs sheets to form a dense composite structure; further XRD analysis of the formed film shows the following results: Figure 6 As shown, from Figure 6 It can be seen that, in addition to the characteristic peak of LDHs, at 2θ = 38.3 o , 43.8 o , 54.3 o , 64.2 o Diffraction peaks corresponding to the ZnO (100), (101), (102), (110), and (103) crystal planes appear, indicating that the array-like material growing perpendicular to the LDHs layer plates in the LDHs composite film after the treatment in step (4) is mainly ZnO.

[0057] Example 2

[0058] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy, the preparation method comprising the following steps:

[0059] (1) A magnesium alloy (AZ31) was mechanically polished with 600#, 1500#, and 3000# silicon carbide sandpaper in sequence, and then ultrasonically cleaned in acetone, 95% ethanol solution, and deionized water in sequence. After cleaning, it was blown dry to obtain a pre-treated magnesium alloy substrate;

[0060] (2) placing the magnesium alloy substrate pre-treated in step (1) in an alkaline solution (the alkaline solution is a 1 mol / L sodium hydroxide solution) and immersing it at 90° C. for 2 h; after the immersion, taking it out and ultrasonically cleaning it with deionized water, and then drying it;

[0061] (3) vertically immersing the magnesium alloy after drying in step (2) into a first hydrothermal growth solution (in the first hydrothermal growth solution, zinc nitrate hexahydrate is 3 mmol / L, urea is 30 mmol / L, sodium ethylenediaminetetraacetate is 50 mmol / L, the solvent is deionized water, and the pH value of the first hydrothermal growth solution is adjusted to 9.5 with 1 wt% ammonia solution), then transferring the system to a stainless steel autoclave lined with tetrafluoroethylene, then sealing the autoclave and placing it in an oven at 90° C. for 24 h to perform a first hydrothermal reaction; after the first hydrothermal reaction is completed, taking out the magnesium alloy and washing it with boiled and cooled deionized water, and finally drying it in an oven at 60° C. for 2 h;

[0062] (4) vertically immersing the magnesium alloy dried in step (3) into a second hydrothermal growth solution (the preparation method of the second hydrothermal growth solution is: mixing a 10 mmol / L deionized water solution of zinc nitrate hexahydrate and polyethyleneimine, wherein the molar ratio of zinc nitrate hexahydrate to polyethyleneimine is 1:1, and then adjusting the pH value of the second hydrothermal growth solution to 9 with a 1 wt % ammonia solution), and then transferring the system to a stainless steel autoclave lined with tetrafluoroethylene, and then sealing the autoclave and placing it in an oven at 85° C. for 8 h to carry out a second hydrothermal reaction; after the second hydrothermal reaction is completed, cooling to room temperature, taking out the magnesium alloy and washing it with deionized water that has been boiled and cooled, and finally drying it naturally.

[0063] Example 3

[0064] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy, the preparation method comprising the following steps:

[0065] (1) A magnesium alloy (AZ31) was mechanically polished with 600#, 1500#, and 3000# silicon carbide sandpaper in sequence, and then ultrasonically cleaned in acetone, 95% ethanol solution, and deionized water in sequence. After cleaning, it was blown dry to obtain a pre-treated magnesium alloy substrate;

[0066] (2) placing the magnesium alloy substrate pre-treated in step (1) in an alkaline solution (the alkaline solution is a 1 mol / L sodium hydroxide solution) and immersing it at 70° C. for 4 h; after the immersion, taking it out and ultrasonically cleaning it with deionized water, and then drying it;

[0067] (3) vertically immersing the magnesium alloy after drying in step (2) into a first hydrothermal growth solution (in the first hydrothermal growth solution, zinc nitrate hexahydrate is 2 mmol / L, urea is 50 mmol / L, sodium ethylenediaminetetraacetate is 30 mmol / L, the solvent is deionized water, and the pH value of the first hydrothermal growth solution is adjusted to 10 with a 1 wt % ammonia solution), then transferring the system to a stainless steel autoclave lined with tetrafluoroethylene, then sealing the autoclave and placing it in an oven at 110° C. for 12 h to perform a first hydrothermal reaction; after the first hydrothermal reaction is completed, taking out the magnesium alloy and washing it with boiled and cooled deionized water, and finally drying it in an oven at 60° C. for 2 h;

[0068] (4) vertically immersing the magnesium alloy dried in step (3) into a second hydrothermal growth solution (the preparation method of the second hydrothermal growth solution is: mixing a 30 mmol / L deionized water solution of zinc nitrate hexahydrate and polyethyleneimine, wherein the molar ratio of zinc nitrate hexahydrate to polyethyleneimine is 1:1, and then adjusting the pH value of the second hydrothermal growth solution to 8 with a 1 wt % ammonia solution), then transferring the system to a stainless steel autoclave lined with tetrafluoroethylene, and then sealing the autoclave and placing it in an oven at 90° C. for 6 h to perform a second hydrothermal reaction; after the second hydrothermal reaction is completed, cooling to room temperature, taking out the magnesium alloy and washing it with deionized water that has been boiled and cooled, and finally drying it naturally.

[0069] Example 4

[0070] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (2), the immersion temperature is 60°C.

[0071] Example 5

[0072] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and the embodiment 1 is that in step (2), the immersion temperature is 100°C.

[0073] Example 6

[0074] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (2), the molar concentration of the solute in the alkaline solution is 4 mol / L.

[0075] Example 7

[0076] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (3), the temperature of the first hydrothermal reaction is 80°C.

[0077] Example 8

[0078] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (3), the temperature of the first hydrothermal reaction is 120°C.

[0079] Example 9

[0080] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (3), the time of the first hydrothermal reaction is 28 hours.

[0081] Example 10

[0082] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that in step (3), the molar concentration of zinc ions in the first hydrothermal growth solution is 0.5 mmol / L.

[0083] Embodiment 11

[0084] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (3), the molar concentration of zinc ions in the first hydrothermal growth solution is 4 mmol / L.

[0085] Example 12

[0086] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (4), the temperature of the second hydrothermal reaction is 75°C.

[0087] Embodiment 13

[0088] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (4), the temperature of the second hydrothermal reaction is 105°C.

[0089] Embodiment 14

[0090] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (4), the time of the second hydrothermal reaction is 10 hours.

[0091] Embodiment 15

[0092] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (4), the molar concentration of zinc nitrate hexahydrate is 5 mmol / L.

[0093] Example 16

[0094] The embodiment of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and embodiment 1 is that in step (4), the molar concentration of zinc nitrate hexahydrate is 40 mmol / L.

[0095] Comparative Example 1

[0096] The comparative example of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy, and the preparation method comprises the following steps:

[0097] (1) A magnesium alloy (AZ31) was mechanically polished with 600#, 1500#, and 3000# silicon carbide sandpaper in sequence, and then ultrasonically cleaned in acetone, 95% ethanol solution, and deionized water in sequence. After cleaning, it was blown dry to obtain a pre-treated magnesium alloy substrate;

[0098] (2) placing the magnesium alloy substrate pretreated in step (1) in an alkaline solution (the alkaline solution is a 1 mol / L sodium hydroxide solution) and immersing it at 80° C. for 4 h; after immersion, taking it out and ultrasonically cleaning it with deionized water, and then drying it;

[0099] (3) vertically immersing the magnesium alloy after drying in step (2) into a first hydrothermal growth solution (in the first hydrothermal growth solution, urea is 40 mmol / L, sodium ethylenediaminetetraacetate is 10 mmol / L, the solvent is deionized water, and the pH value of the first hydrothermal growth solution is adjusted to 10.5 with a 1 wt% ammonia solution), then transferring the system to a stainless steel autoclave lined with tetrafluoroethylene, then sealing the autoclave and placing it in an oven at 105° C. for 20 h to perform a first hydrothermal reaction; after the first hydrothermal reaction is completed, taking out the magnesium alloy and washing it with deionized water that has been boiled and cooled, and finally drying it in an oven at 60° C. for 2 h;

[0100] The SEM images of the obtained surface composite membrane are shown in Figure 7 As shown, from Figure 7 It can be seen that when zinc element is not introduced, the voids in the obtained surface composite film are larger.

[0101] Comparative Example 2

[0102] The comparative example of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy, and the preparation method comprises the following steps:

[0103] (1) A magnesium alloy (AZ31) was mechanically polished with 600#, 1500#, and 3000# silicon carbide sandpaper in sequence, and then ultrasonically cleaned in acetone, 95% ethanol solution, and deionized water in sequence. After cleaning, it was blown dry to obtain a pre-treated magnesium alloy substrate;

[0104] (2) placing the magnesium alloy substrate pretreated in step (1) in an alkaline solution (the alkaline solution is a 1 mol / L sodium hydroxide solution) and immersing it at 80° C. for 4 h; after immersion, taking it out and ultrasonically cleaning it with deionized water, and then drying it;

[0105] (3) vertically immersing the magnesium alloy after drying in step (2) into a first hydrothermal growth solution (in the first hydrothermal growth solution, urea is 40 mmol / L, sodium ethylenediaminetetraacetate is 10 mmol / L, the solvent is deionized water, and the pH value of the first hydrothermal growth solution is adjusted to 10.5 with a 1 wt% ammonia solution), and then transferring the system to a stainless steel autoclave lined with tetrafluoroethylene, and then sealing the autoclave and placing it in an oven at 105° C. for 20 h to perform a first hydrothermal reaction; after the first hydrothermal reaction is completed, taking out the magnesium alloy and washing it with boiled and cooled deionized water, and finally drying it in an oven at 60° C. for 2 h;

[0106] (4) vertically immersing the magnesium alloy dried in step (3) into a second hydrothermal growth solution (the preparation method of the second hydrothermal growth solution is: mixing 20 mmol / L zinc nitrate hexahydrate and polyethyleneimine, wherein the molar ratio of zinc nitrate hexahydrate to polyethyleneimine is 1:1, and then adjusting the pH value of the second hydrothermal growth solution to 8.5 with 1 wt % ammonia solution), then transferring the system to a stainless steel autoclave lined with tetrafluoroethylene, then sealing the autoclave and placing it in an oven at 95° C. for 6 hours to perform a second hydrothermal reaction; after the second hydrothermal reaction is completed, cooling to room temperature, taking out the magnesium alloy and washing it with deionized water that has been boiled and cooled, and finally drying it naturally;

[0107] The SEM images of the obtained surface composite membrane are shown in Figure 8 As shown, from Figure 8 It can be seen that ZnO nanoparticles are randomly deposited in the interstices of LDHs sheets and attached to the gaps between LDHs and the surface of the layers (tending to be on the top).

[0108] Comparative Example 3

[0109] The comparative example of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and comparative example 2 is that in step (4), the temperature is maintained at 95° C. for 12 h;

[0110] The SEM images of the obtained surface composite membrane are shown in Fig. 9 As shown, from Fig. 9 It can be seen that the ZnO nanocolumns grow in the gaps of the LDHs sheets to form a nanocolumn cluster structure with irregular orientation (random orientation) (tending to the top).

[0111] Comparative Example 4

[0112] The comparative example of the present invention provides a method for preparing a composite film on the surface of a magnesium alloy. The only difference between the preparation method and Example 1 is that step (2) is not included.

[0113] Effect example

[0114] Effect Examples of the Invention The performance of the magnesium alloy surface composite film prepared in the embodiments and comparative examples is investigated, including the following aspects:

[0115] 1. Porosity of the composite film on the surface of the magnesium alloy: According to the SEM microscopic morphology of the composite film on the surface of the magnesium alloy prepared in the embodiment and the comparative example, the obtained composite film morphology is imported into the Image J image processing software to set a fixed image area, and the proportion of the pore area is calculated to obtain the porosity of the sample;

[0116] 2. Pitting corrosion resistance: The magnesium alloy surface composite film samples prepared in the examples and comparative examples were used as anodes, platinum electrodes as cathodes, and calomel electrodes as reference electrodes. Anode polarization electrochemical tests were performed using an electrochemical workstation to obtain the anode polarization curves and record the turning point E of the sudden increase in the anode branch corrosion current. pit (pitting point);

[0117] The obtained results are shown in Table 1;

[0118] Table 1

[0119] Porosity / % <![CDATA[E pit / V]]> Porosity / % <![CDATA[E pit / V]]> Example 1 7.2 0.82 Embodiment 11 8.6 0.65 Example 2 7.5 0.68 Example 12 14.2 0.28 Example 3 7.1 0.73 Embodiment 13 9.6 0.54 Example 4 10.7 0.46 Embodiment 14 8.9 0.63 Example 5 9.8 0.43 Embodiment 15 12.5 0.52 Example 6 11.5 0.34 Example 16 9.8 0.57 Example 7 10.5 0.42 Comparative Example 1 28.4 -0.12 Example 8 12.4 0.31 Comparative Example 2 16.7 0.04 Example 9 11.8 0.47 Comparative Example 3 20.3 -0.06 Example 10 13.8 0.51 Comparative Example 4 22.6 -0.02

[0120] It can be seen from Table 1 that the composite film on the surface of the magnesium alloy prepared by the preparation method of the present invention has a low porosity of less than 14.2%, a high pitting corrosion resistance, and a pit The positive offset value is above 0.28V;

[0121] It can be seen from Example 1 and Comparative Examples 2-3 that when zinc ions are not introduced into the first hydrothermal growth solution, the porosity of the composite membrane prepared subsequently is higher, and the corrosion resistance of the composite membrane obtained is significantly deteriorated; it can be seen from Example 1 and Comparative Example 4 that when alkali treatment is not performed first, the porosity of the composite membrane obtained is significantly increased, and the corrosion resistance is also significantly reduced;

[0122] The comparison of the anodic polarization curves of the LDHs film on the magnesium alloy surface prepared in Example 1 and Comparative Example 3 is shown in the figure below: Fig.10 shown; from Fig.10 It can also be clearly seen that the typical corrosion current "sudden increase" feature is observed in the anodic polarization curve of Comparative Example 3 (LDHs film enclosed by conventional ZnO nanocolumns), indicating that under this condition, the pitting potential of the LDHs film layer is 0.1%, that is, pitting pits appear under the film layer; while for the composite film prepared in Example 1, E corrThe positive shift is to -0.13V, and the self-corrosion current density is also significantly lower than the former; that is, compared with the LDHs film enclosed by zinc oxide nanocolumns in Comparative Example 3, the preparation method of the composite film provided by the present invention not only improves the density of the film layer (physical barrier effect on the corrosive medium), but also enhances its corrosion resistance.

[0123] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a LDHs film on a magnesium alloy surface, characterized in that: The preparation method comprises the following steps: (1) Pretreating the magnesium alloy substrate; (2) immersing the magnesium alloy substrate pretreated in step (1) in an alkaline solution, followed by pickling, water washing, and drying; (3) placing the magnesium alloy dried in step (2) in a first hydrothermal growth solution to perform a first hydrothermal reaction, and washing and drying after the first hydrothermal reaction is completed; (4) placing the magnesium alloy dried in step (3) in a second hydrothermal growth solution for a second hydrothermal reaction, and washing and drying after the second hydrothermal reaction is completed; The solutes of the first hydrothermal growth solution include zinc salt, urea and sodium ethylenediaminetetraacetate, and the solvent is deionized water; The solute of the second hydrothermal growth solution includes zinc nitrate hexahydrate and polyethyleneimine, and the solvent is deionized water.

2. The preparation method according to claim 1, characterized in that: In the step (1), the pretreatment includes mechanically polishing the magnesium alloy substrate using silicon carbide sandpaper, washing with acetone, ethanol and deionized water in sequence after polishing, and then drying.

3. The preparation method according to claim 1, characterized in that: In the step (2), the solute of the alkaline solution includes potassium hydroxide and / or sodium hydroxide, and the molar concentration of the solute is 0.5-2 mol / L.

4. The preparation method according to claim 1, characterized in that: In the step (2), the immersion temperature is 70-90° C. and the immersion time is 2-4 hours.

5. The preparation method according to claim 1, characterized in that: The zinc salt includes at least one of zinc nitrate and zinc acetate.

6. The preparation method according to claim 1, characterized in that: In the step (3), in the first hydrothermal growth solution, the molar concentration of zinc ions is 1-3 mmol / L, the molar concentration of urea is 30-50 mmol / L, and the molar concentration of sodium ethylenediaminetetraacetate is 10-50 mmol / L; and the pH value of the first hydrothermal growth solution is 9.5-10.

5.

7. The preparation method according to claim 1, characterized in that: In the step (3), the temperature of the first hydrothermal reaction is 90-110° C., and the time of the first hydrothermal reaction is 12-24 hours.

8. The preparation method according to claim 1, characterized in that: In the step (4), the molar concentration of zinc nitrate hexahydrate in the second hydrothermal growth solution is 10-30 mmol / L; and the pH value of the second hydrothermal growth solution is 8-9.

9. The preparation method according to claim 1, characterized in that: In the step (4), the temperature of the second hydrothermal reaction is 85-95° C., and the time of the second hydrothermal reaction is 4-8 hours.

Citation Information

Cited By

  • Method for treating surfaces, and associated bodies and uses

    WO2026201982A1